Mutations in NaV1.5 Reveal Calcium-Calmodulin Regulation of Sodium Channel - Nof, Eyal; Vysochek, Leonid; Meisel, Eshcar; Burashnikov, Elena; Antzelevitch, Charles; Clatot, Jerome; Beinart, Roy; Luria, David; Glikson, Michael; Oz, Shimrit (Frontiers in Physiology, 2019)
Mutations in the SCN5A gene, encoding the cardiac voltage-gated sodium channel NaV1.5, are associated with inherited cardiac arrhythmia and conduction disease. Ca2+-dependent mechanisms and the involvement of β-subunit (NaVβ) in NaV1.5 regulation are not fully understood. A patient with severe sinus-bradycardia and cardiac conduction-disease was genetically evaluated and compound heterozygosity in the SCN5A gene was found. Mutations were identified in the cytoplasmic DIII-IV linker (K1493del) and the C-terminus (A1924T) of NaV1.5, both are putative CaM-binding domains. These mutants were functionally studied in human embryonic kidney (HEK) cells and HL-1 cells using whole-cell patch clamp technique. Calmodulin (CaM) interaction and cell-surface expression of heterologously expressed NaV1.5 mutants were studied by pull-down and biotinylation assays. The mutation K1493del rendered NaV1.5 non-conductive. NaV1.5K1493del altered the gating properties of co-expressed functional NaV1.5, in a Ca2+ and NaVβ1-dependent manner. NaV1.5A1924T impaired NaVβ1-dependent gating regulation. Ca2+-dependent CaM-interaction with NaV1.5 was blunted in NaV1.5K1493del. Electrical charge substitution at position 1493 did not affect CaM-interaction and channel functionality. Arrhythmia and conduction-disease -associated mutations revealed Ca2+-dependent gating regulation of NaV1.5 channels. Our results highlight the role of NaV1.5 DIII-IV linker in the CaM-binding complex and channel function, and suggest that the Ca2+-sensing machinery of NaV1.5 involves NaVβ1 and more than one monomeric NaV1.5 channel.